Sustainable intensification and household dietary diversity in maize-based farming systems of Zambia and Zimbabwe - Ngoma, Hambulo; Simutowe, Esau; Manyanga, Mark; Thierfelder, Christian L. (SAGE Publications, 2023)
With only four years before the end date for the United Nations Decade of Action on Nutrition, the need to identify nutrition-sensitive and sustainable agricultural interventions that can address hunger and malnutrition cannot be more urgent. This paper assesses associations between sustainable intensification practices and dietary diversity in maize-based farming systems of Zambia and Zimbabwe. Using survey data from 1124 households, we apply an instrumental variable approach that allows to control for the fact that farmers self-select themselves into adopting sustainable intensification practices, making adoption endogenous. We also explore pathways from intensification to dietary diversity. We find significant positive associations between the adoption intensity of sustainable intensification practices (SIPs) such as minimum tillage, minimum tillage and crop rotation, and minimum tillage and intercrops and improved production and crop diversity and in turn, dietary diversity on average. These findings hinge on there being widespread adoption of SIPs. There is need for concerted efforts to address current bottlenecks that hinder widespread adoption and promote broader food group diversification to realize the nutrition related co-benefits associated with sustainable intensification.